Sultanate of Bilah: Cultural Heritage and Its Impact on Local Identity in Labuhanbatu - Safitri, Elen; Dora, Nuriza (FKIP - Universitas Riau, 2025)
The aim of this research is to determine the impact of the legacy of the Bilah Sultanate on local identity in Labuhanbatu today. The Bilah Sultanate was an Islamic kingdom that was founded in the 17th century and played an important role in the spread of religion, culture and political influence in the region. However, over time, traces of the history and cultural heritage of the Bilah Sultanate have experienced significant fading. This research uses a descriptive qualitative approach with data collection techniques through observation and in-depth interviews with descendants of the sultanate, traditional leaders and local communities. The research results show that although physical heritage such as mosques and royal artifacts still exist, the preservation of intangible cultural heritage such as the Pilando dance, Malay humming, and culinary specialties such as raja pudding and labar-buas are starting to be forgotten. The lack of documentation, weak involvement of local governments, and lack of understanding by the younger generation have resulted in a disconnection in the collective memory of local identity that is rooted in the Sultanate of Bilah.